O gênero crônica sob a perspectiva transcriativa de Belkiss Spenzieri Carneiro de Mendonça: uma análise de "Andanças no tempo" - Mendonça, Simone Carneiro de (2021)
This research aims an inventory of the literary genre chronicle and attempts to have different points of views from some theorists and literature critics. Next, there is a point in checking the historical evolution in Brazil of this gender, especially in the State of Goiás, and how its production worked in the middle of the twentieth century in the State. Last, but not least, elightens the name of the pianist, writer and artist Belkiss Spenzieri Carneiro de Mendonça. First of all, on chapter one there is a concern why this genre is so less studied at the Universities and schools as a whole. And that point brings us to the reasoning why there are so few writers that dedicate their lives to the chronicles instead, they consolidate their names in the other genres of literature such as the novels, short-stories and poetry. On chapter two, the focus is on the Transcriation theory as the fine line of the research and its intersignification between the past and present times and how it permits a dialogue between the memory and the daily life, topics very well discussed in the chronicles. The authors studied of the research remains on the texts of Haroldo de Campos, the transcriation precussor and also João Carlos Tedesco who talks about the relation between history and memory. On chapter three, there is an analysis from eight chronicles from the book Andanças no Tempo by Belkiss Spenzieri Carneiro de Mendonça in which dialogues with other goiano's writers such as Bernardo Élis and Marietta Telles Machado in their respective books. The methodology would be concentrated in the book reading. For this research some critics and theorists would have been studied such as Nelson Werneck Sodré, José Guilherme Merchior, Carlos Nejar, Antonio Candido, Luiz Roncari, Massaud Moisés, Davi Arrigucci, Afrânio Coutinho, Hênio Tavares, Alfredo Bosi among others. As a result, this dissertation searches for: making an inventory of this gender, showing its historical evolution, but more important analyzing and divulguing the chronicles in Goiás, specially from the book Andanças no tempo by Belkiss Spenzieri Carneiro de Mendonça revealing how important this is for the Literature and Critics field and also bringing up the importance of a great, mutifaceted reader, musician, writer and artist from our society